Usage of Slang in Bangladeshi Dramas: An Overview of Viewers' Perspectives - Rana, Shohel; Hossain, Emran; Reza, Shibbir Ahmad; Jahan, Faria (Journal of Journalism and Media, 2024)
This study aims to explore the influence of slang on audience behavior and its persuasive effects on individuals. A quantitative method, especially a survey was employed to investigate the impact of slang on viewer behavior, with 103 participants. This study focuses on examining the impact of slang within the context of Bangladeshi dramas. The concerning aspects of slang used in dramas, whereas, among all respondents, 59.2% agreed that contents on YouTube incorporate slang, with comedy dramas accounting for 68.9% of this usage. Furthermore, 49.5% of the dramas analysed use slang during the scenes of controversy. Some 46.6% of the viewers surveyed in this study expressed their belief that the younger generation adopts and imitates slang. The study also highlights the negative consequences associated with slang usage in dramas. The respondents said that 47.6% of the slang portrayed in dramas exhibits a malicious attitude towards women. Moreover, 93.2% of the participants claimed that slang contribute to the destruction of standard Bangla language. Additionally, 45.6% of the respondents opined that uses of slang in dramas encourage cyberbullying in society.